Research on failure properties and analysis methods of Q690D based on energy characteristics of AE signal - Jinjin Zhai; Yuantao Sun; Yingcheng Li; Qing Zhang; Xiaoqing Chang (Scientific Reports)
Abstract The bearing properties of high-strength steel (HSS) structures determine their safety, and the energy conversion and mechanical state evolution during their failure process are closely related. Therefore, determining the corresponding relationship between micro failure characteristics and macro mechanical state changes is of great significance for structural safety monitoring. In this paper, the acoustic-mechanical energy characteristic relationship during the tensile failure process of Q690 HSS is studied based on acoustic emission (AE) technology. The distribution law of characteristic parameters of AE signals during the Q690D tensile test is analyzed based on the AE mechanism, and the energy conversion characteristics of Q690 HSS failure process are determined from time- and space-dimension through the AE energy parameter. Besides, based on the mechanical state of the specimens during the loading process, combined with strain signals and finite element analysis, the failure process was divided into multiple intervals. Finally, a comparative analysis was conducted to obtain the relationship and variation rules between the macroscopic mechanical state changes and acoustic characteristics, which provides a reference for the application of AE energy signals in the state monitoring of Q690 structures.